Leg stiffness and muscle power vs manometer in sportswomen with symptoms of stress urinary incontinence - Pires, T.; Pires, P.; Moreira, H.; Gabriel, R.; Reis, A.; Viana, S.; Viana, R. (Clinical Biomechanics, 2021)
Highlights